PENERAPAN ACTION DAN RESULT CONTROL UNTUK MENGATASI CONTROL PROBLEM PADA ROCKET CHICKEN MANGGIS DI BANJARMASIN - Priska Birgitta Wijaya; Ria Sandra Alimbudiono (Perpustakaan Universitas Surabaya, 2018)
Competition in the business world, especially the franchise business is getting tighter because the prerequisites and business categories are easily accepted by the public. In order for a business to survive to compete and achieve the desired goals, the business entity must be able to show good performance through management control system. One form of management control is the formal control of action and result control. So, in this study was conducted with the aim to know the implementation of management control system that is action and result control to overcome the control problem in order to achieve the desired goal of business entity. This research uses qualitative approach, applied research and explanatoryresearch method. The object of this research is one outlet Rocket Chicken which is a local franchise business in the field of fast food restaurant is Rocket Chicken Manggis in Banjarmasin. Data collection used in this research is interview, observation and document analysis. From this study, researchers found some control problems that occur in Rocket Chicken Manggis in Banjarmasin and analyze the causes and impacts that occur from the control problem. Control problems that occur in general are lack of direction, motivational problems, and personal limitations. To solve this problem, the researcher gives action design and result control to overcome control problem in each form of control to improve employee performance.